PELATIHAN LITERASI LAPORAN KEUANGAN SEDERHANA BAGI UMKM LEGOK: DAMPAK PADA PRAKTIK PENCATATAN DAN PROFITABILITAS - Rahmiyanti, Sev; Ranggala, Qadar; Indra, Jasmi; Indradi, Donny; Suhatman, Zaldi; Nurmiyanti, Leni; Sajid, Muhamad Roid; Wajo, Fauzan; Meidina, Frida Tri; Fawwaz, Muhammad Irvan (Universitas Mataram, 2025)
The 2025 Community Service Program (KKN) of Universitas Cendekia Abditama (UCA) in Legok District focused on providing simple financial report literacy training for Micro, Small, and Medium Enterprises (MSMEs). Many MSME actors in this area lack basic knowledge and skills in recording financial transactions and preparing essential financial statements such as income statements and cash flow reports. This program aimed to enhance the financial management capabilities of local businesses to support more informed business decision-making. The implementation method included seminars, technical training sessions, and direct assistance using a participatory approach to ensure active engagement of participants. The results showed a significant improvement in participants’ understanding and application of simple financial recording techniques. They became more capable of calculating profits, monitoring cash flow, and evaluating their business performance. Several MSMEs began to adopt more systematic financial practices. This training effectively contributed to increased profitability and strengthened the economic independence of the Legok community. Therefore, the program demonstrated a positive impact on MSME empowerment through the improvement of basic financial literacy.